Reduction of Uric Acid Levels with Bay Leaf Decoction in Patients with Gout Arthritis - Kharisna, Dendy; Yulinda, Riska Dwi Mai; Yanti, Sri; Azhar, Bayu; Arfina, Angga (Global Health Science Group, 2024)
Gout Arthritis is a disease caused when the kidneys are unable to remove uric acid in the blood. This results in the accumulation of uric acid levels which manifests in inflammation in the joints and has a physical and psychological impact on the sufferer. One of the complementary therapies used to reduce uric acid levels is the use of bay leaf boiled water. The purpose of the study was to determine the effect of bay leaf decoction on uric acid levels in patients with gout atritis in the working area of the Payung Sekaki Health Center, Pekanbaru City. The research design used quasy was experimental with a time series design with control. The sample in this study was 18 people with gout who were taken using the purposive sampling technique and were differentiated into the intervention and control groups. The intervention group was given bay leaf decoction for 4 days and uric acid levels were measured before and after the administration of the leaf decoction. The instruments used were observation sheets and GCU easy touch tools. The data were analyzed using t-dependent and t-independent tests. The results of the study in the intervention group were obtained p values on day 1 (0.000), day 2 (0.000), day 3 (0.000) and day 4 (0.000). All of these results showed a p value of <0.05 which means that there was a significant effect of giving bay leaf decoction on reducing uric acid levels in the intervention group. Meanwhile, in the control group, p values were obtained which were <0.05 respectively starting from the 1st day (0.609), the 2nd day (0.870), the 3rd day (0.910), and the 4th day (0.377). Based on these findings, there was no difference in pre-test and post-test scores in the control group. The results of the t-independent test in the intervention group and the control group from days 1 to 4 obtained the same p value of 0.000 (<0.05). This means that the difference in post-test scores after being given bay leaf decoction water in the intervention and control groups. Thus, it can be concluded that giving bay leaf decoction regularly until the 4th day can help reduce uric acid levels in patients with gout arthritis.